Integrated personalized diabetes management goes Europe: A multi-disciplinary approach to innovating type 2 diabetes care in Europe. Issue 2 (April 2021) - Jones, Allan; Bardram, Jakob Eyvind; Bækgaard, Per; Cramer-Petersen, Claus Lundgaard; Skinner, Timothy; Vrangbæk, Karsten; Starr, Laila; Nørgaard, Kirsten; Lind, Nanna; Bechmann Christensen, Merete; Glümer, Charlotte; Wang-Sattler, Rui; et al.
Highlights: Public-private partnership for technology, education, and business creation. Digital approach to assess the unique needs of persons with type 2 diabetes. Collection of patient reported outcome measures (PROMs) in primary care. Active contribution to enabling value-based healthcare in Europe. Abstract: Type 2 diabetes mellitus represents a multi-dimensional challenge for European and global societies alike. Building on an iterative six-step disease management process that leverages feedback loops and utilizes commodity digital tools, the PDM-ProValue study program demonstrated that integrated personalized diabetes management, or iPDM, can improve the standard of care for persons living with diabetes in a sustainable way. The novel "iPDM Goes Europe" consortium strives to advance iPDM adoption by (1) implementing the concept in a value-based healthcare setting for the treatment of persons living with type 2 diabetes, (2) providing tools to assess the patient's physical and mental health status, and (3) exploring new avenues to take advantage of emerging big data resources.